2015
DOI: 10.7224/1537-2073.2014-015
|View full text |Cite
|
Sign up to set email alerts
|

Managing Neuropsychological Impairment in Multiple Sclerosis

Abstract: These preliminary results suggest that MaTiMS represents a feasible psychological group training program that may foster improvements in self-efficacy, fatigue, and mood. The next step will be an evaluation of the program in a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 37 publications
0
6
0
3
Order By: Relevance
“…Some researchers have started examining this topic. For example, when patients with multiple sclerosis tend to adopt a dysfunctional metacognitive strategy, metacognition can become a relevant therapeutic tool (Pöttgen et al, 2015). The results of a recent study showed insignificant differences between metacognitive factors of multiple sclerosis patients and healthy subjects.…”
Section: Introduction Rationalementioning
confidence: 99%
“…Some researchers have started examining this topic. For example, when patients with multiple sclerosis tend to adopt a dysfunctional metacognitive strategy, metacognition can become a relevant therapeutic tool (Pöttgen et al, 2015). The results of a recent study showed insignificant differences between metacognitive factors of multiple sclerosis patients and healthy subjects.…”
Section: Introduction Rationalementioning
confidence: 99%
“…Vor dem Hintergrund fehlender standardisierter Verfahren wurde jüngst eine standardisierte Intervention vorgestellt (Metacognitive Training in MS, MaTiMS) , die die relevanten neuropsychologischen Komponenten wie Aufmerksamkeit, Gedächtnis, Fatigue, Stress, Depression und Einfüh-lung berücksichtigt (Pottgen et al 2015). Die Ergebnisse der Pilotstudie wiesen auf einen positiven Effekt der Intervention hinsichtlich Selbstwirksamkeit, Verbesserung der Fatigue und Lebensqualität der Teilnehmer hin (Pottgen et al 2015).…”
Section: Neuropsychologische Rehabilitationunclassified
“…Die Ergebnisse der Pilotstudie wiesen auf einen positiven Effekt der Intervention hinsichtlich Selbstwirksamkeit, Verbesserung der Fatigue und Lebensqualität der Teilnehmer hin (Pottgen et al 2015).…”
Section: Neuropsychologische Rehabilitationunclassified
“…Vor dem Hintergrund fehlender standardisierter Verfahren wurde jüngst eine standardisierte Intervention vorgestellt (Metacognitive Training in MS, MaTiMS) , die die relevanten neuropsychologischen Komponenten wie Aufmerksamkeit, Gedächtnis, Fatigue, Stress, Depression und Einfühlung berücksichtigt (Pottgen et al 2015). Die Ergebnisse der Pilotstudie wiesen auf einen positiven Effekt der Intervention hinsichtlich Selbstwirksamkeit, Verbesserung der Fatigue und Lebensqualität der Teilnehmer hin (Pottgen et al 2015).…”
Section: Icd-10-codeunclassified